Immobilized enzyme/single-wall carbon nanotube composites for amperometric glucose detection at very low applied potential - LYONS, MICHAEL EDWARD (Royal Chemical Society, 2008)
The behaviour of support electrodes modified with randomly dispersed single-wall carbon nanotube meshes containing adsorbed glucose oxidase with respect to amperometric glucose detection at a low potential is demonstrated.
PUBLISHED
Keywords: Chemistry